Psoriasis vulgaris in Chinese individuals is associated with PSORS1C3 and CDSN genes - Chang, Y.T.; Chou, C.T.; Shiao, Y.M.; Lin, M.W.; Yu, C.W.; Chen, C.C.; Huang, C.H.; Lee, D.D.; Liu, H.N.; Wang, W.J.; Tsai, S.F. (British journal of dermatology (1951), 2006)
Summary Background  Besides the HLA‐Cw*0602 allele, the psoriasis susceptibility 1 candidate 3 (PSORS1C3) and corneodesmosin (CDSN) genes are two probable psoriasis susceptibility genes in the PSORS1 locus. The −79C, −26C and +246A alleles of the PSORS1C3 gene, the CDSN*971T allele, CDSN*TTC (619T–1236T–1243C) and CDSN*5 (619T–1240G–1243C) are strongly associated with psoriasis in the caucasian population. Until now, no haplotype study of the PSORS1C3 and CDSN genes has been documented in Chinese patients with psoriasis vulgaris. Objectives  We aimed to determine whether genetic polymorphisms of the PSORS1C3 and CDSN genes were associated with an increased risk of psoriasis vulgaris in Chinese patients in Taiwan. Methods  We investigated the PSORS1C3 and CDSN genes for disease association by direct sequencing in 178 patients with psoriasis vulgaris and 203 control subjects. Genotyping for HLA‐Cw*0602, α‐helix coiled‐coil rod homologue (HCR) gene and single nucleotide polymorphism (SNP) n.9 was also carried out using a sequence‐based typing method. Results  The PSORS1C3*582A allele, an SNP in the 3′‐untranslated region of the PSORS1C3 gene, was a major psoriasis vulgaris susceptibility allele in the Chinese population, and the association was much stronger in patients with early‐onset psoriasis vulgaris (22·3% vs. 6·9%, odds ratio = 3·87, Pc =0·0000072). The frequencies of CDSN*TTC and CDSN*971T were also significantly increased in patients with early‐onset psoriasis vulgaris. Moreover, PSORS1C3*582A, SNP n.9*C, Cw*0602 and HCR*WWCC were in near complete linkage disequilibrium (LD) with each other; in contrast, the LD with the CDSN gene was not so strong. SNP n.9*C–Cw*0602–PSORS1C3*582A–HCR*WWCC was a major susceptibility haplotype in patients with early‐onset psoriasis vulgaris (P < 10−7) and this risk haplotype also carried CDSN*TTC and CDSN*971T. Conclusions  The PSORS1C3 and CDSN genes are important psoriasis susceptibility genes in Chinese patients with psoriasis vulgaris.